Voluntary counseling and testing (VCT) services and their contribution to access to HIV diagnosis in Brazil Contribuição dos Centros de Testagem e Aconselhamento (CTA) para o acesso ao diagnóstico da infecção pelo HIV no Brasil - Alexandre Grangeiro; Maria Mercedes Escuder; Maria Amélia Veras; Draurio Barreira; Dulce Ferraz; Jorge Kayano (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2009)
The Voluntary Counseling and Testing (VCT) Network was implemented in Brazil in the 1980s to promote anonymous and confidential access to HIV diagnosis. As a function of the population and dimensions of the local epidemic, the study assessed the network's coverage, using data from a self-applied questionnaire and data from the Information Technology Department of the Unified National Health System (SUS), UNDP, and National STD/AIDS Program. The Student t test was used for comparison of means and the chi-square test for proportions. Brazil has 383 VCT centers, covering 48.9% of the population and 69.2% of the AIDS cases. The network has been implemented predominantly in regions where the epidemic shows a relevant presence, but 85.3% of the cities with high HIV incidence lack VCT centers; absence of VCT was associated with more limited health infrastructure and worse social indicators. A slowdown in expansion of the network was observed, with VCT Centers implemented on average 16 years after the first AIDS case in the given municipality. The number of HIV tests performed under the SUS is 2.3 times higher in cities with VCT centers. The network's scope is limited, thus minimizing the contribution by these services to the supply of HIV diagnosis in Brazil. A rede nacional de Centros de Testagem e Aconselhamento (CTA) foi implantada no Brasil nos anos 1980 para promover, anônima e confidencialmente, o diagnóstico do HIV. Em função da população abrangida e das dimensões da epidemia local, o estudo avaliou a cobertura dessa rede, utilizando dados de questionário auto-aplicado e de bancos de informações do DATASUS, PNUD e Programa Nacional de DST e AIDS. Aplicou-se teste t para comparações de média e qui-quadrado para proporções. Existem no Brasil 383 CTA, abrangendo 48,9% da população e 69,2% dos casos de AIDS. A rede está predominantemente implantada em regiões em que a epidemia é relevante, entretanto 85,3% das cidades com alta incidência não possuem CTA; ausência associada à menor estrutura de saúde e piores indicadores sociais. Observa-se desaceleração na expansão da rede, sendo um CTA implantado, em média, 16 anos após o primeiro caso de AIDS no município. O número de testes realizados no SUS é 2,3 vezes maior em cidades com CTA. A abrangência da rede é reduzida, minimizando a contribuição desses serviços na oferta do diagnóstico do HIV no Brasil.